Correction: Neurodevelopmental performance among pre-schoolers treated for severe anaemia at Lira Regional Referral Hospital, Uganda. - PLOS ONE Staff (PLoS ONE, 2021)
[This corrects the article DOI: 10.1371/journal.pone.0240694.].